(untitled) (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
Author Mr. Mushraff Ali Khan M, Associate Professor, Department of Pharmaceutics, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, India Abstract Pharmaceutics converts an active pharmaceutical ingredient into effective dosage forms through scientific principles of drug delivery. Dosage form design balances pharmacological requirements with patient factors, creating solid forms (tablets, capsules), liquid preparations, semisolids, and specialized delivery systems, each requiring specific formulation approaches addressing stability, release kinetics, and manufacturing scalability. Drug absorption mechanisms determine therapeutic effectiveness through complex processes influenced by physicochemical properties, physiological variables, and formulation factors, with bioavailability measures quantifying the fraction of administered drug reaching systemic circulation. Novel drug delivery systems extend beyond conventional formulations to provide targeted delivery, controlled release, and enhanced stability through liposomal encapsulation, nanoparticle carriers, transdermal patches, implantable systems, and 3D-printed medications tailored to individual patient needs. Pharmaceutical excipients serve essential functions beyond merely completing formulations, acting as diluents, binders, disintegrants, lubricants, coating materials, preservatives, and solubilizers, with careful selection required to ensure compatibility, stability, and proper drug release while avoiding potential allergic reactions or interactions. Keywords: Formulation; Drug Release; Delivery Systems; Physicochemical Properties; Product Development VIEW PDF